A comparative assessment of efficacy for pain relief and quality of life between dienogest and combined oral contraceptive pills in endometriosis patients in Eastern India - Priyanka Kumari; Rathindra Nath Ray; Sandip Sarkar; Sohini Ghosh Dastidar; Yogesh Munde (MGM Journal of Medical Sciences)
Background: This study aimed to compare the effectiveness of dienogest (DNG) and combined oral contraceptive (COC) pills in alleviating pain among patients with endometriosis in Eastern India. Materials and Methods: A prospective, hospital-based, observational comparative study was conducted at R. G. Kar Medical College and Hospital in Kolkata, India, from March 2021 to August 2022. The study included two groups: Group A (dienogest 2 mg/day, n = 115) and Group B (combined oral contraceptive pills, Mala-N, n = 115). Pain levels were assessed using the Visual Analog Scale (VAS), and the quality of life (QoL) was evaluated with the Endometriosis Health Profile Questionnaire (EHP-5 PRO) after 3 and 6 months of treatment. Results: The mean age ± standard deviation was 32.57 ± 8.02 years in Group A and 32.89 ± 7.92 years in Group B. After 6 months, Group A showed a significant reduction in pelvic pain (P = 0.001), whereas Group B did not experience a significant improvement (P = 0.55). A significant difference in pain reduction was observed between the two groups after 6 months (P = 0.0001). Both treatments resulted in slight improvements in the quality of life, but the difference between the groups was not statistically significant. Conclusion: Both dienogest and COC pills may assist in managing endometriosis-related pain and enhancing the quality of life, with dienogest showing superior pain relief. These medications appear to be safe and effective options for managing endometriosis.